An integrated approach to pharmacotherapy in smoking cessation: the role of varenicline, bupropion, cytisine, and nicotine replacement therapy - Więcław, Kacper; Stańko, Katarzyna; Piasek, Laura; Szafran, Adrianna; Wiśniewska, Klaudia; Ostańska, Agnieszka; Terelak, Wiktor; Ciechański, Marcin; Witkowska, Edyta; Godek, Grzegorz (Journal of Education, Health and Sport, 2023)
Introduction: Smoking tobacco is a significant global health issue, contributing to various diseases, including heart disease, cancer, and respiratory disorders. Quitting smoking is not only a beneficial decision for an individual’s health but also for society as a whole. Pharmacological therapy plays a crucial role in the smoking cessation process by supporting and increasing the chances of success. Aim: To compare four medications used in smoking cessation: varenicline, bupropion, cytisine, and nicotine replacement therapy, in terms of their characteristics, mechanism of action, efficacy, and adverse effects. Materials and Methods: A review of available data in the PubMed database regarding medications registered in Poland for the treatment of nicotine addiction. Key Results: The efficacy of all four medications in smoking cessation was demonstrated. Individuals using varenicline, bupropion, cytisine, or nicotine replacement therapy had higher chances of quitting smoking compared to placebo groups. Specifically, varenicline showed the highest efficacy among all the medications studied. Despite a high level of safety profile, each therapy can cause various adverse effects, with the most serious being the risk of seizures associated with bupropion. Conclusions: Varenicline, bupropion, cytisine, and nicotine replacement therapy are valuable tools in the process of smoking cessation and increase the chances of successfully quitting the addiction. The choice of a specific medication may depend on individual patient preferences and clinical factors. These findings should be taken into consideration when making therapeutic decisions in the field of smoking cessation.